Relative sea-level changes and crustal movements in Britain and Ireland since the Last Glacial Maximum. (15th May 2018) - Shennan, Ian; Bradley, Sarah L.; Edwards, Robin
Abstract: The new sea-level database for Britain and Ireland contains >2100 data points from 86 regions and records relative sea-level (RSL) changes over the last 20 ka and across elevations ranging from ∼+40 to −55 m. It reveals radically different patterns of RSL as we move from regions near the centre of the Celtic ice sheet at the last glacial maximum to regions near and beyond the ice limits. Validated sea-level index points and limiting data show good agreement with the broad patterns of RSL change predicted by current glacial isostatic adjustment (GIA) models. The index points show no consistent pattern of synchronous coastal advance and retreat across different regions, ∼100–500 km scale, indicating that within-estuary processes, rather than decimetre- and centennial-scale oscillations in sea level, produce major controls on the temporal pattern of horizontal shifts in coastal sedimentary environments. Comparisons between the database and GIA model predictions for multiple regions provide potentially powerful constraints on various characteristics of global GIA models, including the magnitude of MWP1A, the final deglaciation of the Laurentide ice sheet and the continued melting of Antarctica after 7 ka BP. Highlights: New sea-level database for Britain and Ireland with >2100 data points from 86 regions. Records of relative sea-level (RSL) changes over the last 20 ka across elevations ranging from ∼+40 to −55 m. RSL data show good agreement with the broad patterns of RSL change predicted by glacial isostatic adjustment (GIA) models. No clear evidence across regions, ∼100-500 km scale, of decimetre- and centennial-scale oscillations in sea level. Constrains features of global GIA models, including MWP1A, final deglaciation of Laurentia, Antarctic melting post 7 ka BP.